90 éves a Magyar Tudományos Akadémia Ökológiai Kutatóközpont Balatoni Limnológiai Intézete - Fésüs, László (Gerundium, 2018)
The Lake Balaton Institute of Limnology of the Ecological Research Centre of the Hungarian Academy of Arts and Sciences is 90 years old. The Balaton Limnology Institute of the Hungarian Academy of Arts and Sciences celebrated the 90th anniversary of its opening on the 8th of September, 2017, in Tihany, where László Fésüs, chairman of the Biology Section of the Hungarian Academy of Sciences greeted the event with the address printed here. The institute, originally called "The Hungarian Biology Research Institute" was the very first independent research institution in Hungary, established and opened in 1927 by the famous politician Kúnó Klébelsberg who is also highly respected for developing university campuses and many new elementary schools. During nine decades the institute attracted leading life scientists from Hungary as well as abroad, its research areas covered the major trends in biology including broad topics in botany, zoology, molecular biology, neurobiology and has had a crucial role saving Lake Balaton from ecological catastrophes.